The Asian bond markets initiative policy maker achievements and challenges. (Asian Development Bank, 2017)
The Asian Bond Markets Initiative (ABMI) was launched in December 2002 by the Association of Southeast Asian Nations (ASEAN) and the Peoples Republic of China, Japan, and the Republic of Korea collectively known as ASEAN+3 to strengthen financial stability and reduce the region vulnerability to the sudden reversal of capital flows.This paper also provides recommendations for addressing new sources of market volatility and other challenges within and outside the framework of the Asian Bond Markets Initiative.